Perceived Injustice Moderates the Relationship between Pain and Depressive Symptoms among Individuals with Persistent Musculoskeletal Pain - Whitney Scott; Michael Sullivan (Pain Research and Management)
BACKGROUND: Numerous investigations report that depressive symptoms frequently coexist with persistent pain. However, evidence suggests that symptoms of depression are not an inevitable consequence of pain. Diathesis-stress formulations suggest that psychological factors interact with the stress of pain to heighten the risk of depressive symptoms. Perceptions of injustice have recently emerged as a factor that may interact with the stress of pain to increase depressive symptoms.